Modified Direct Anterior Approach for Total Hip Arthroplasty in an Indonesian Population with Primary Standard Instruments of Total Hip Arthroplasty: Our Experiences and Short-term Follow-up - Septiawan, Eko Medio; Laurentia, Claudia Bella; Al Mashur, Muslich Idris (Indonesian Hip and Knee Society (IHKS), 2023)
The direct anterior approach (DAA) for total hip arthroplasty (THA) is a very sophisticated and complicated surgery typically performed using a specialized operating room table and instruments. In our clinic, this procedure was performed with a modified incision to avoid dependence on a special operating room table and we could use ordinary THA instruments. There is an obvious absence of literature regarding this subject. The method in this study a total of 31 patients (31 hips) were recruited for primary THAs from January 1, 2020 to December 31, 2021 who underwent THAs using the DAA in the supine position with modified incision. The technical feasibility and early results were evaluated. The results is orientation of the acetabular component average cup inclination was 41.57o ±6.7o, (23o-57o) and the mean cup anteversion was 17.36o ± 5o, (11o-38o). The incidence of neutral coronal femoral stem alignment were 30 hips (97%), varus was 1 (3%), neutral sagittal alignment were 30 hips (97%), and flexion was 1 (3%). The preoperative Harris Hip Score (HHS) was 57.89 points (range: 17-68 points), whereas the postoperative HHS was 89.97 points (range: 82-100 points). There were no postoperative problems such as proximal femur fracture, hematoma, superficial wound complications, deep vein thrombosis, lateral femoral cutaneous nerve damage, heterotopic ossification, loosening of the acetabular component, loosening of the stem, dislocation, infection, or postoperative periprosthetic fracture. Conclusion DAA supine for THA with modified incision may be a valuable alternative in the absence of a special operating room table or special instruments for DAA. This technique also seems to provide satisfactory clinical and radiographic outcomes with acceptable complications in our early follow-up.